2011
DOI: 10.1007/s00436-011-2796-3
|View full text |Cite
|
Sign up to set email alerts
|

Multiple effects of pepstatin A on Trypanosoma cruzi epimastigote forms

Abstract: Herein, we have aimed to explore the effects of pepstatin A, a powerful aspartic protease inhibitor, on Trypanosoma cruzi, the etiologic agent of Chagas' disease. Pepstatin A arrested the proliferation of epimastigotes of T. cruzi (clone Dm28c, TcI lineage), in both dose- and time-dependent manner. The IC(50) value was calculated to be 36.2 μM after 96 h of parasite-drug contact. The parasite treatment with pepstatin A resulted in significant morphological alterations, including parasites becoming round in sha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
11
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 42 publications
2
11
0
Order By: Relevance
“…The HIV PIs induced several alterations on epimastigote forms similar to those caused by pepstatin A, a prototypal aspartic peptidase inhibitor [12] . Due the morphological alterations observed after treatment with the HIV PIs by light microscopy, we aimed to analyze the T. cruzi clone Dm28c epimastigotes alterations more deeply by means of transmission electron microscopy.…”
Section: Discussionmentioning
confidence: 96%
See 4 more Smart Citations
“…The HIV PIs induced several alterations on epimastigote forms similar to those caused by pepstatin A, a prototypal aspartic peptidase inhibitor [12] . Due the morphological alterations observed after treatment with the HIV PIs by light microscopy, we aimed to analyze the T. cruzi clone Dm28c epimastigotes alterations more deeply by means of transmission electron microscopy.…”
Section: Discussionmentioning
confidence: 96%
“…In trypanosomatids, it has been observed that the aspartic peptidase inhibitors commonly used in HAART were capable of suppressing the proliferation of Leishmania species [26] - [28] . In an initial approach to study the effects of aspartic peptidase inhibitors against T. cruzi , we have previously demonstrated that the classic aspartic peptidase inhibitor pepstatin A was able to inhibit T. cruzi clone Dm28c epimastigote growth in a typical dose-dependent manner, with an IC 50 value of 36.2 µM after 96 h [12] . In the present work, we showed that HIV PIs inhibited the proliferation of T. cruzi clone Dm28c epimastigotes at much lower concentrations than pepstatin A, being ritonavir, lopinavir and nelfinavir the most effective compounds tested.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations